2015
DOI: 10.5792/ksrr.2015.27.3.156
|View full text |Cite
|
Sign up to set email alerts
|

High-Flexion Total Knee Arthroplasty Using NexGen LPS-Flex System: Minimum 5-year Follow-up Results

Abstract: PurposeThis study is to report clinical and radiological results of high-flexion total knee arthroplasty (TKA) using NexGen LPS-flex system at a minimum 5-year follow-up, and to analyze the implant survivorship based on the results.Materials and MethodsA total of 80 patients (118 knees) who underwent patellar preserving TKA using NexGen LPS-flex implant between February 2007 and February 2008 and could be followed for minimum 5 years were reviewed. The range of motion (ROM), hip-knee-ankle angle, Knee Society … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 30 publications
1
9
0
Order By: Relevance
“…Normal values for the α, β, and δ angles are not well defined in the literature. However, our results were comparable with values in other studies [ 11 , 12 ].…”
Section: Discussionsupporting
confidence: 92%
“…Normal values for the α, β, and δ angles are not well defined in the literature. However, our results were comparable with values in other studies [ 11 , 12 ].…”
Section: Discussionsupporting
confidence: 92%
“…These results are consistent with those previously reported on literature with this implant. 8,9,22 MB-TKA has different theoretical advantages over fixed-bearing surfaces. First of all, there is an increased implant conformity without increasing the interface stresses, resulting in aseptic loosening.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Kim et al failed to find any clinical difference between LPS flex and conventional TKA after a long-term follow-up and reported favorable outcomes and a 10-year survival rate of 99 % [ 17 ]. Rhee et al also reported that high-flexion TKA yielded satisfactory clinical and radiological outcomes with a 99.2 % implant survival rate at 5 years postoperatively [ 18 ].…”
Section: Discussionmentioning
confidence: 99%